A Study of the Problems in Using Near-Synonymous Words in Chinese Among Undergraduate Students Majoring in Chinese - Praparkarn, Porramin; Kandee, Wareekorn; Pengge, Li; Hasup, Ketkanok (Journal of Roi Et Rajabhat University, 2025)
The objectives of this study were 1) to investigate the problems of using synonymous words in Chinese among undergraduate students majoring in Chinese, and 2) to propose solutions to the causes of misuse as well as approaches for enhancing learning. The participants were 97 undergraduate students majoring in Chinese from two universities in Thailand, selected through purposive sampling. The research instruments consisted of a questionnaire and a vocabulary test on Chinese synonyms. Data were analyzed using content analysis, frequency, and percentage. The results revealed that the largest group of students (36 students, accounting for 37.11%) obtained scores ranging from 175 to 209 points, indicating that most students still lacked a complete understanding and appropriate application of synonymous words in Chinese. The findings further demonstrated that: 1) the majority of students faced difficulties in selecting the correct synonymous word in context. The primary causes were: 1.1) the influence of their mother tongue (Thai), leading to literal translation, 1.2) rote memorization rather than contextual understanding, and 1.3) insufficient systematic instruction on synonym differentiation. 2) The recommended pedagogical approaches included synonym-based comparative instruction, the use of authentic communicative situations, and learner training to recognize and self-correct errors. This study highlights the importance of instructional design that emphasizes deep contextual understanding rather than rote learning in order to foster sustainable development of learners’ Chinese language proficiency.